Marketing Strategy of New Schools in the Selection of New Students at AL Zamzam Sukodono Islamic Elementary School - Muhammad Handoyo; Nurdyansyah Nurdyansyah; Budi Haryanto (International Consortium of Education and Culture Research Studies, 2020)
This study aims to determine: 1. New school marketing strategies in selecting new students in Al Zamzam Sukodono Islamic elementary school. 2. Constraints faced in implementing the new school marketing strategy in the selection of new students in Al Zamzam Islamic elementary school. This research was conducted using qualitative methods. Research data collected by observation, documentation and interviews, then analyzed using the inductive approach. This research was conducted at Al Zamzam Islamic Elementary School, Address Kedung, Jumputrejo Sukodono Sidoarjo. This school was only established in 2018 with the first batch of 24 students. The results of this study indicate that: The marketing strategy of a new school in the selection of new students at the Al Zamzam Sukodono Islamic elementary school, which starts from the: Planning stage, includes Market Identification, Segmenting, Targetting, and Positioning, which is used to determine marketing including time plans , date of implementation, target segment, marketing area, marketing implementation techniques and implementation team. Organizing, is organizing work including: determining job description with the new admissions committee (PPDB) as executor, organizing marketing strategies and organizing marketing resources of educators. Actuating, is a form of principal's work in directing or indirectly directing the marketing of Islamic education by using various strategies adapted to situations and conditions. Controlling, is the final form and evaluation that is not only carried out at the end, but in the process, so that the marketing strategy that is carried out can be updated following market developments and needs. The results of this study can be used as material for thought, information and input on the implementation of new school marketing in managing education marketing and developing marketing strategies in the future. as well as this research as consideration for carrying out evaluations and planning of school marketing strategies that have been running, as well as references in the field of education, especially education management for further writing.